Effect of hypertonic saline treatment on the inflammatory response after hydrochloric acid-induced lung injury in pigs - Carla Augusto Holms; Denise Aya Otsuki; Marcia Kahvegian; Cristina Oliveira Massoco; Denise Tabacchi Fantoni; Paulo Sampaio Gutierrez; Jose Otavio Costa Auler Junior (Clinics, 2015)
OBJECTIVES:Hypertonic saline has been proposed to modulate the inflammatory cascade in certain experimental conditions, including pulmonary inflammation caused by inhaled gastric contents. The present study aimed to assess the potential anti-inflammatory effects of administering a single intravenous dose of 7.5% hypertonic saline in an experimental model of acute lung injury induced by hydrochloric acid.METHODS:Thirty-two pigs were anesthetized and randomly allocated into the following four groups: Sham, which received anesthesia and were observed; HS, which received intravenous 7.5% hypertonic saline solution (4 ml/kg); acute lung injury, which were subjected to acute lung injury with intratracheal hydrochloric acid; and acute lung injury + hypertonic saline, which were subjected to acute lung injury with hydrochloric acid and treated with hypertonic saline. Hemodynamic and ventilatory parameters were recorded over four hours. Subsequently, bronchoalveolar lavage samples were collected at the end of the observation period to measure cytokine levels using an oxidative burst analysis, and lung tissue was collected for a histological analysis.RESULTS:Hydrochloric acid instillation caused marked changes in respiratory mechanics as well as blood gas and lung parenchyma parameters. Despite the absence of a significant difference between the acute lung injury and acute lung injury + hypertonic saline groups, the acute lung injury animals presented higher neutrophil and tumor necrosis factor alpha (TNF-α), interleukin (IL)-6 and IL-8 levels in the bronchoalveolar lavage analysis. The histopathological analysis revealed pulmonary edema, congestion and alveolar collapse in both groups; however, the differences between groups were not significant. Despite the lower cytokine and neutrophil levels observed in the acute lung injury + hypertonic saline group, significant differences were not observed among the treated and non-treated groups.CONCLUSIONS:Hypertonic saline infusion after intratracheal hydrochloric acid instillation does not have an effect on inflammatory biomarkers or respiratory gas exchange.